2005
DOI: 10.1177/0021998305050426
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Delamination Growth and Opening Near Intersection of Transverse Matrix Cracks and Delamination

Abstract: The use of advanced composite materials for cryogenic fuel tanks reduces the mass of the structure but microscopic damage can cause fuel leakage. The amount of leakage depends on the connectivity of the damage and crack opening displacements. In this paper, the damage growth and the opening near the intersection of transverse matrix cracks (TMC) and a delamination are discussed. Three-dimensional finite element analysis (FEA) was used to analyze cross-ply and angle-ply graphite/epoxy laminates. The strain ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Zubillaga et al [8] experimentally observed that matrix cracks often trigger the onset of interlaminar delamination due to the stress concentration at the crack tips. A similar observation was found by Noh et al [9] who predicted the shape and size of the delamination through finite element (FE) analysis. Although coupled failure behavior of composite laminates between matrix cracks and delamination has been observed in experiments, accurate modelling of this phenomenon for application in composite structures remains challenging.…”
Section: Introductionsupporting
confidence: 82%
“…Zubillaga et al [8] experimentally observed that matrix cracks often trigger the onset of interlaminar delamination due to the stress concentration at the crack tips. A similar observation was found by Noh et al [9] who predicted the shape and size of the delamination through finite element (FE) analysis. Although coupled failure behavior of composite laminates between matrix cracks and delamination has been observed in experiments, accurate modelling of this phenomenon for application in composite structures remains challenging.…”
Section: Introductionsupporting
confidence: 82%
“…Models have been introduced to predict the damage state, i.e. crack density and delamination length, from the loading history and the material properties [4,[6][7][8][9][10][11][12]. Damage state and current loading can then be used as input for crack opening displacement prediction [10,11,13], and also for permeability prediction [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%